Vitamin D insufficiency is associated with metabolic syndrome independent of insulin resistance and obesity in young adults ‐ The Berlin Aging Study II. Issue 8 (30th April 2021) - Buchmann, Nikolaus; Eckstein, Nils; Spira, Dominik; Demuth, Ilja; Steinhagen‐Thiessen, Elisabeth; Norman, Kristina
Abstract: Purpose: Age‐related changes affect vitamin D absorption and metabolism. Low 25‐hydroxyvitamin D concentrations have been reported as risk factor for the development of metabolic syndrome (MetS). However, recent evaluations suggest this association might be explained by obesity or insulin resistance (IR) in subjects with MetS. Our aim was to analyze associations between vitamin D insufficiency and MetS in a young cohort without diabetes and two senior cohorts with and without diabetes. Methods: Four hundred sixteen young and 1357 older BASE‐II participants were analyzed. Type 2 diabetes (T2D) was defined according to European Society of Cardiology (ESC) guidelines, MetS as suggested by International Diabetes Federation/American Heart Association/National Heart, Lung and Blood Institute (IDF/AHA/NHLBI 2009). Vitamin D insufficiency was defined as 25‐hydroxyvitamin D concentrations <50 nmol/L. Among other confounders, BMI and IR were taken into account. Results: MetS was prevalent in 7.7% of the young and in 35.6% of the older BASE‐II participants and T2D occurred in 12.7% of the older participants. In young subjects without diabetes, vitamin D insufficiency was associated with an independent 3.2‐fold increased odds of having MetS (OR: 3.2 CI: 1.0–8.7; p  = 0.042). However, in the older participants, this association was lost once BMI was taken into account among those with diabetes, and once IR was taken into account among those without diabetes. Conclusion: Independent associations between vitamin D insufficiency and MetS were only found among young subjects without diabetes. In the older adults, BMI annihilated these associations among subjects without diabetes as did HOMA‐IR among subjects with diabetes.